Character Education Values of Primary School Students in the Denias Senandung di atas Awan Movie by John De Rantau - Nur Azmi Alwi; Lindri Martinopa; Yulia Maulani; Feby Kharisna (STAI Hubbulwathan Duri, 2022)
The background of this research is related to several deviations in the character of primary school students. Thus, it is necessary to provide educational media that can be imitated. This study analyzes the values of character education from Denias Senandung Di atas Awan movie by John De Rantau that primary school-age students can imitate. Qualitative research is a research approach used with the type of documentary research, which is one type of research in qualitative. Documentation technique is used for collecting data which contain writings related to the plot of the story in the movie under study. Data analysis in this study uses content analysis. Ten character values were found in the movie as the content of character education values which were the character values of honesty, disciplined, creativity, independence, democracy, national spirit, patriotism, friendly/communicative, peace-loving, and responsible. Children from the movie Denias Senandung Di atas Awan can imitate these 10 points of character education